Acerola's clones of industrial interest - Da Moto, J. C.; De Assis, S. A.; Pecin, J.; De Lima, G.; Martins, ABG; Oliverira, OMMD (Blackwell Publishing, 2005)
In order to know which clone of acerola is better for acerola industrialization, we studied the pectin methylesterase (PME) specific activity, pectin content and vitamin C content in five different clones of acerola. The pectin yield varied from 1.37 to 2.99% and the highest content of pectin occurred in clones 3 and 5. Ascorbic acid varied significantly from 1157.5 to 1735.5 mg/100 g of pulp in the five clones. The highest content of vitamin C occurred in clone 4. The PME specific activity varied from 0.79 to 2.92 units g(-1)/g of pulp and the highest values occurred in clone 2. We also studied the optimum temperature and the optimum pH of this enzyme. Clones 1, 2, 4 and 5 showed optimum temperature at 90C. Clone 3 showed practically the same specific activity at all temperatures studied. Clones 1 and 4 showed an optimum pH of 9.0 and clone numbers 2, 3 and 5 showed a pH optimum at 8.5.
Keywords: acerola; ascorbic acid; pectin; pectin methylesterase